Economic operation strategy of an electricity–heat coupling system considering complementary low-carbon characteristics of source-load - Tang, Jianlin; Xiao, Yanhong; Qian, Bin; Hu, Houpeng; Zhou, Mi; Ou, Jiaxiang; Wang, Ji; Chen, Ruize (Frontiers in Energy Research, 2024)
The operation effect of source-side carbon capture power plant (CCPP) and power-to-gas (P2G) equipment does not match, the response range of load-side traditional demand response strategy is small and the adjustment period is limited, which leads to the problem that the complementary potential of low-carbon characteristics on both sides of the source and load is not fully utilized. This paper proposes an electricity-heat coupling system scheduling strategy considering the complementary lowcarbon characteristics of 'source-load'. Firstly, the low-carbon operation characteristics of CCPP and P2G with the integrated flexible operation are analyzed, and the source-side CCPP-P2G comprehensively flexible operation mode is proposed. Secondly, based on the characteristics of flexible adjustment and mutual substitution of electricity and heat load, a load-side comprehensive demand response method is proposed. Finally, the complementary mechanism of low-carbon characteristics on both sides of the source and load is analyzed, and the low-carbon economic dispatch model of the electricity-heat coupling system is constructed to realize the 'source-load' collaborative low-carbon operation. The simulation analysis verifies that the proposed strategy can give full play to the energy time shift advantages of the source-side CCPP and P2G, and improve the economic and environmental benefits of the system operation.